Three-pronged sustainability assessment of ten towns in the vicinity of Bangkok, Thailand - Viriya Taecharungroj; Pheereeya Boonchaiyapruek; Morakot Muthuta (My University, 2019)
The purpose of the current research is to develop a method that assesses the levels of sustainability in towns in Thailand from various dimensions and multiple perspectives. The three-pronged assessment illustrates the integration of the three perspectives, namely, those of residents, the physical reality, and the local government; such an integration is important yet limited in the existing literature. This assessment also attempts to overcome some of the challenges of sustainability indicators, including comparability, dynamism, availability, comprehensibility, effectiveness, and sufficiency. The scope of this study consists of ten towns in the six provinces in the vicinity of Bangkok, which are at risk of sprawling development from Bangkok. To determine the levels of resident perceptions, the authors used a cluster random sampling method to collect data from 2157 respondents. Thirty-six indicators were used to assess the physical reality. Regarding the investments of the local government, 488 projects of the 10 towns were categorised based on the 11 dimensions of place sustainability. Towns can use this method to monitor the efficiency of investments over time and to plan more effective investments. A workshop was organised for towns to adjust project planning according to the Four-Action Framework.
Keywords: Comparability; Scope (computer science); Dynamism; Action plan; Urban Planning and Valuation